2009
DOI: 10.1099/mic.0.021477-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes required for different stages of dendritic swarming in Bacillus subtilis, with a novel role for phrC

Abstract: Highly branched dendritic swarming of B. subtilis on synthetic B-medium involves a developmental-like process that is absolutely dependent on flagella and surfactin secretion. In order to identify new swarming genes, we targeted the two-component ComPA signalling pathway and associated global regulators. In liquid cultures, the histidine kinase ComP, and the response regulator ComA, respond to secreted pheromones ComX and CSF (encoded by phrC) in order to control production of surfactin synthases and ComS (com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
51
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 71 publications
5
51
0
1
Order By: Relevance
“…Recent studies [8], using genetic analysis and fluorescent microscopy to measure the level of production (expression) from the gene encoding the major flagellum subunit in situ, have identified a specific subpopulation of hyper-flagellated cells ('swarmers' ). These are dominant in the formation of buds and then subsequently spearhead dendrites in the tips.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies [8], using genetic analysis and fluorescent microscopy to measure the level of production (expression) from the gene encoding the major flagellum subunit in situ, have identified a specific subpopulation of hyper-flagellated cells ('swarmers' ). These are dominant in the formation of buds and then subsequently spearhead dendrites in the tips.…”
Section: Resultsmentioning
confidence: 99%
“…Some labs have tested swarming motility on LB medium in which tryptone was replaced by an equal amount of peptone (13). We reproduced the "LB" medium containing peptone and found that whereas strain 3610 was swarming proficient, strain 168 was swarming deficient (Fig.…”
mentioning
confidence: 98%
“…In some cases of the reported swarming of strain 168, plates were poured 1 h before use, dried for 5 min, and incubated at 60 to 70% humidity (13). When 0.7% agar LB plates were freshly poured and not dried, we noticed that toothpick inoculation of the cells disturbed the agar surface and caused a pool of water to well forth from the agar (see Fig.…”
mentioning
confidence: 99%
“…For those experiments, alternative methods, such as flow cytometry or colony thin sectioning, are used (27,28). In some cases, macroscopic colonies can still be subjected to microscopy, but only when images are taken at the colony edge, where there is a monolayer of cells, or when the colonies are dissected before microscopy (28)(29)(30)(31)(32)(33). Studies that perform microscopy on macroscopic colonies typically show qualitative results, such as representative images with fluorescent overlays (e.g., see the work of Fall et al [29] and López et al [32]).…”
mentioning
confidence: 99%